Is feline lymphoma worth managing differently? - Aworinde, Anne Adesola (2021)
zone lymphoma). There are few reports that determine whether immunophenotype confers any prognostic value in cats. A number of other factors have been proposed by several studies however, many have only assessed specific types of lymphomas such as GI, nasal and CNS lymphomas, reporting variable survival rates.